Dampak Pembangunan Sarana Perdagangan dan Jasa Terhadap Kondisi Sosial Lingkungan Permukiman Kabupaten Gowa, Provinsi Sulawesi Selatan - Adinda Febriyanti; Shirly Wunas; Mimi Arifin (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2020)
The development of the city can be seen by the growth of supporting facilities for diverse community activities, it can be characterized by the increasingly dense population and buildings, the more complete city facilities that support the social and economic activities of the community. The research aims to identify the development impact of trading and service facilities to environmental conditions and the social condition of the community, and determining the strategy of improving the quality. This research started from October 2019 to January 2020, located in Aorepala Housing and BTN Pao-Pao Permai. Data is obtained through observation methods, documentation, questionnaires and interviews. Analysis in a spatial descriptive, qualitative descriptive, and SWOT analysis. The results showed that the impact of the development of trade and services facilities significantly affect the environment, there is a change in land function 6-45% in the period of 10 years (2010-2019). It increased the social interactions of local people and have made it easier to achieve efficient as well as a more consumptive lifestyle change. The strategy to improve the quality of the environment and social conditions of the community is the procurement of trade facilities and services in accordance with the social strata of the community, development of infrastructure services and supporting facilities in economic activities, increasing reforestation and development and management and improvement of accessibility, and supporting the smooth running of transportation nodes.